PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI KECAMATAN TAMPAN, KOTA PEKANBARU - Takziah, Jumiatun; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research is to develop a street children's family educationmodule in terms of the aspects of material clarity, material systematic, image support,compatibility of material delivery time and material completeness. This type of researchis development research to produce a design but is not followed by testing the product.The educational module material was validated by 2 BK FKIP UR lecturers, and 2Counseling Guidance Teachers. Educational material consists of 4 modules namely,module 1: understanding parenting and family functions, module 2: being a responsibleparent, module 3: the role of parents educating children and module 4: the role ofparents in preventing children from going down to the street. From the value given byexperts for the material clarity aspect, a score of 4.5 was obtained with a very clearcategory, for systematic aspects of the material a score of 5 was obtained with a verysystematic category, for the aspect of image support a score of 4.75 was obtained with avery supportive category, for the aspect of compatibility the delivery time of thematerial was obtained a score of 4.25 with a very suitable category and for the aspectsof completeness of the material obtained a score of 4.25 with a very complete category.Whereas for all aspects of the material assessment, it shows that the material developedhas fulfilled the expected criteria with the acquisition of a score of 4.5, which iscategorized as very good. As for the suggestions given by the validator are: each quoteis included with the source, clarify each material again, pay attention again to thewriting of the material, and add conclusions.Keywords: Module, Education, Street Children